2021
DOI: 10.3390/pharmacy9010024
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of the Medication Use Process by People with Intellectual Disabilities. What a Pharmacist Should Know!

Abstract: There is a scarcity of information about the experience of people with intellectual disabilities in the medication use process. Six people with intellectual disabilities consented to be interviewed by a pharmacist to determine their knowledge and views of medication use. Data from semi-structured interviews were analysed using a grounded theory approach. Self-determination and risk to the quality of the medication use process were identified as theories. Literature review provided two explanations—vulnerabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Medication adherence has been defined as ‘the extent to which patients take medications as prescribed by their healthcare providers’, 71 while its measurement is the process of systematically assigning numbers or words to tangible and intangible characteristics so that they can be defined, quantified and differentiated. In our review of 59 PROMs, these self-reported measures aimed at quantifying medication adherence based on the responses from a nominal or Likert-point scale and assigning categories to the total scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medication adherence has been defined as ‘the extent to which patients take medications as prescribed by their healthcare providers’, 71 while its measurement is the process of systematically assigning numbers or words to tangible and intangible characteristics so that they can be defined, quantified and differentiated. In our review of 59 PROMs, these self-reported measures aimed at quantifying medication adherence based on the responses from a nominal or Likert-point scale and assigning categories to the total scores.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of diseases or statuses explored were asthma, 61 diabetes, AIDS, 58 hypertension, 57 68 chronic diseases, acute osteoporosis, eye-related conditions, 16 cardiovascular, and organ transplant recipients. 27 59 DISCUSSION Quantification of adherence and non-adherence Medication adherence has been defined as 'the extent to which patients take medications as prescribed by their healthcare providers', 71 while its measurement is the process of systematically assigning numbers or words to tangible and intangible characteristics so that they can be defined, quantified and differentiated. In our review of 59 PROMs, these self-reported measures aimed at quantifying medication adherence based on the responses from a nominal or Likert-point scale and assigning categories to the total scores.…”
Section: Extent Of Non-adherencementioning
confidence: 99%
“…Straetmans et al (2007) have shown that the high number of prescriptions to people with intellectual disabilities is a consequence of more frequent contacts with GPs, even though people with ID are less likely to receive a prescription during a doctor's appointment. Another reason possibly explaining the differences in the use of medicines between people with ID and the control group is that people with ID are less likely to assess or decide for themselves whether they want to take the medicines prescribed to them (Flood & Henman 2021). Because register data do not provide an answer, further research on the subject is needed.…”
Section: Discussionmentioning
confidence: 99%
“…During osteoporosis evaluations the experience may pose difficulties due to the lack of reasonable adjustments and challenges with equipment, or individuals may simply be scared. People with ID have had complications in the past getting tested for osteoporosis because of the nature of the DXA test that may seem frightening or challenging for this population [38][39][40]. In frequent patient-physician interactions, the diagnosis itself proves to be more challenging because those with ID are often unable to express their symptoms or frightened by the DXA assessment [41].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that the use of the GE Lunar Achilles quantitative Ultrasound (QUS) has the potential to be a much better alternative to the DXA for people with IDs, allowing for the undiagnosed and untested population to be more adequately monitored [6]. Nonetheless, after being diagnosed, some individuals have difficulty following through on their treatment plans and may find it challenging to adhere to physical therapy regimes, medications such as bisphosphonates or understanding the importance of the treatment due to lack of reasonable adjustments [37][38][39][40]. As mentioned above, osteoporosis is not a topic associated with men with intellectual disability, further exacerbating the demand for more attention.…”
Section: Introductionmentioning
confidence: 99%